DEVELOPING A LESSON PLAN FOR TEACHING ENGLISH FOR SPECIFIC PURPOSES TO ADULT LEARNERS AT A PRIVATE UNIVERSITY - Ratnawati Ratnawati (JALL (Journal of Applied Linguistics and Literacy), 2017)
Lesson plan is the written procedures of activities in the teachingand learning process. Some components which create lesson plan at leaststandard competence, basic competence, objective, and learning activities,also assessment. An observation found that lesson plan mismatched toteaching and learning process. Consequently, students did not meet goodcompetences in their learning. Considering this condition, the developedlesson plan is highly needed to overcome above problems. This article dealswith R n D research design proposed by Borg and Gall (1983). The steps ofresearch-based design focused on preliminary and information collecting,planning, and develop preliminary product of form. The instrument wasused is interview. The result of this study shown that developed lesson planis more attractive, applicable, and informative than previous one. In linewith result, development is very important in education. Educationaldevelopment is way to build creative and innovative thinking. Also,developing lesson plan is needed to determine the success of teaching andlearning process.Key words: lesson plan, competence, and development